Recycling Hemp Hurd Biowaste Into a High-performance Cellulose Aerogel for Oil Adsorption and Water-in-oil Emulsion Filtration - Zhai, Y; Yuan, X; Jena, KD (Elsevier BV, 2025)
A superhydrophobic aerogel derived from hemp hurd, a low-value byproduct of fibre production, is developed for oil-water mixture separation. The fabrication process involves homogenisation, ultrasonication, freeze-drying, and chemical functionalisation using methyltriethoxysilane, yielding a lightweight, porous structure with exceptional hydrophobicity and oleophilicity. Characterisation using scanning electron microscopy confirms a hierarchical micro-nanostructure, while contact angle measurements show a superhydrophobic behaviour (water contact angles > 150°). The aerogel exhibits exceptional oil absorption performance, with uptake capacities ranging from 56 to 125 g/g for different oils and organic solvents. It also exhibits excellent mechanical compressibility and reusability, maintaining performance over 50 % of the adsorption capacity after ten adsorption-regeneration cycles. Furthermore, the aerogel also demonstrated excellent performance as a filtration medium for water-in-oil emulsion separations, achieving high flux (665–728 l m⁻² h⁻¹) and high separation efficiency (97.8–99.1 %). These findings highlight the potential of these hemp hurd-derived aerogels as scalable and environmentally sustainable materials for oil adsorption and water-in-oil emulsion separation.
Keywords: 40 Engineering; 4016 Materials Engineering; 0703 Crop and Pasture Production; Biotechnology; 3004 Crop and pasture production; 3006 Food sciences; 4004 Chemical engineering; Cellulose; Hydrophobic; Aerogel; Hemp hurd; Oil-Water separation